2020
DOI: 10.1002/jcla.23233
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as diagnostic biomarkers for multiple myeloma and monoclonal gammopathy of undetermined significance

Abstract: Background: Multiple myeloma (MM) is still an incurable hematological malignancy evolved from asymptomatic monoclonal gammopathy of undetermined significance (MGUS). New evidence suggests that circulating microRNAs (miRNAs) can serve as stable diagnostic biomarkers for MM and MUGS.Methods: Serum miRNAs in MM patients, MUGS patients, and healthy controls (HC) were performed by Agilent Bioanalyzer 2100. MicroRNAs in MM detected as promising biomarkers were validated by using quantitative real-time PCR (qRT-PCR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“… Author Year Country microRNAs Regulation mode Sample size Speci-men Diagnostic power MM Healthy Sen (%) Spe (%) AUC Single miRNA Kubiczkova, L. [23] 2014 Czech Republic let-7d Downregulated 103 30 Serum 0.641 0.867 0.804 Kubiczkova, L. [23] 2014 Czech Republic let-7e Downregulated 103 30 Serum 0.888 0.633 0.829 Li, J. [24] 2020 China miR-15a-5p Upregulated 23 18 Serum 0.870 0.610 0.804 Li, F. [25] 2015 China miR-16–1 Downregulated 90 19 Plasma 1.000 0.730 0.864 Hao, M. [26] 2015 China miR-19a Upregulated 108 56 Serum 0.773 0.897 0.910 Qiu, X. Y. [27] 2013 China miR-20a Downregulated 40 20 Plasma …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Author Year Country microRNAs Regulation mode Sample size Speci-men Diagnostic power MM Healthy Sen (%) Spe (%) AUC Single miRNA Kubiczkova, L. [23] 2014 Czech Republic let-7d Downregulated 103 30 Serum 0.641 0.867 0.804 Kubiczkova, L. [23] 2014 Czech Republic let-7e Downregulated 103 30 Serum 0.888 0.633 0.829 Li, J. [24] 2020 China miR-15a-5p Upregulated 23 18 Serum 0.870 0.610 0.804 Li, F. [25] 2015 China miR-16–1 Downregulated 90 19 Plasma 1.000 0.730 0.864 Hao, M. [26] 2015 China miR-19a Upregulated 108 56 Serum 0.773 0.897 0.910 Qiu, X. Y. [27] 2013 China miR-20a Downregulated 40 20 Plasma …”
Section: Resultsmentioning
confidence: 99%
“… [30] 2018 China miR-125b-5p Upregulated 35 20 Plasma 0.860 0.960 0.954 Kubiczkova, L. [23] 2014 Czech Republic miR-130a Downregulated 103 30 Serum 0.575 0.900 0.722 Li, J. [24] 2020 China miR-134-5p Upregulated 23 18 Serum 0.870 0.667 0.812 Hao, M. [26] 2015 China miR-135b-5p Upregulated 108 56 Serum 0.667 0.833 0.810 Nidhi Gupta. [21] 2019 Germany miR-143 Upregulated 30 30 Serum 0.767 0.767 0.854 Nidhi Gupta.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agilent Human, Release 21 (8*60K, Design ID: 070156) was used to analyze miRNA expression in MM and HC group. The samples labeling, hybridization, washing, and data analysis steps were completed according to the previous research 11 …”
Section: Methodsmentioning
confidence: 99%
“…With the rise of miRNAs in recent years, many studies have shown that the accuracy of circulating miRNAs in the early diagnosis of MM is satisfactory but inconsistent [18][19][20][21] . This may be caused by factors such as different detection technologies, platforms, standards, and insu cient clinical samples.…”
Section: MMmentioning
confidence: 99%